2021
DOI: 10.3390/vaccines9040329
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled, Double-Blind Randomized (Phase IIB) Trial of Oral Administration with HPV16 E7-Expressing Lactobacillus, GLBL101c, for the Treatment of Cervical Intraepithelial Neoplasia Grade 2 (CIN2)

Abstract: Cervical intraepithelial neoplasia (CIN), a precursor lesion to cervical cancer, is caused by high-risk human papillomavirus (HPV); high-grade CIN lesions (CIN2-3) are precancerous and require treatment. No globally approved therapy is available for CIN2-3 treatment. This study is a placebo-controlled randomized clinical trial of GLBL101c treatment for CIN2 in 40 patients with HPV16-positive CIN2 who were 1:1 randomized to receive GLBL101c (1 g/daily) or placebo for 5 days at 1, 2, 4, and 8 weeks. No differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…[ 101 ] However, when GLBL101c was administered to the patients with HPV16‐positive CIN2, the E7‐specific Th1 immune responses and the regression rate from CIN3 to CIN2 or less showed no significant statistical difference between GLBL101c and placebo groups. [ 102 ] The unsatisfactory clinical trial results were due to limited expression levels of E7 in CIN2 lesion, and weak antigen‐presentation ability of GLBL101c. Therefore, the next generation of Lactobacillus expressing HPV16 E7 on the cell surface, which is more immunogenic than GLBL101c, is already under clinical research.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…[ 101 ] However, when GLBL101c was administered to the patients with HPV16‐positive CIN2, the E7‐specific Th1 immune responses and the regression rate from CIN3 to CIN2 or less showed no significant statistical difference between GLBL101c and placebo groups. [ 102 ] The unsatisfactory clinical trial results were due to limited expression levels of E7 in CIN2 lesion, and weak antigen‐presentation ability of GLBL101c. Therefore, the next generation of Lactobacillus expressing HPV16 E7 on the cell surface, which is more immunogenic than GLBL101c, is already under clinical research.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…We identified 202 articles, among which, 12 studies published between 2004 and 2021 met the selection criteria (Figure 1). The included studies represented six randomized controlled trials (RCTs) (Ikeda et al 2021; Harper et al 2019; Trimble et al 2015, Kaufman et al 2007 and Garcia et al 2004 ; Choi et al 2020); 14-19 three case-control studies (Rosales et al 2014 and Garcia-Hernandez et al 2006, Corona Gutierrez et al 2004) 20-22 and three single-arm trials (Park et al 2019; Brun et al 2011 and Einstein et al 2007). 23-25 All the included studies recruited women with histology confirmed diagnosis of CIN 2/3.…”
Section: Resultsmentioning
confidence: 99%
“…A recent trial investigated the efficacy and adverse reactions of GLBL101c in patients with CIN 2, the results showed that there were no serious adverse reactions. The CR of GLBL101c and placebo groups were 11% (2/19 cases) and 0% (0/19 cases) respectively, and the effective rate of CR+PR, was 22% ( Ikeda et al., 2021 ). The results show that the clinical efficacy is not ideal and it is necessary to develop new protocols.…”
Section: Research Progress Of Hpv Therapeutic Vaccinesmentioning
confidence: 94%